Unstable fragility fractures of the ankle in the elderly: Transarticular Steinmann pin or external fixation. (August 2017) - Meijer, R.P.J.; Halm, J.A.; Schepers, T.
Highlights: Treatment of ankle fractures in the elderly poses unique challenges. There is no difference in complications between both fixation types. Return to pre-injury mobilization may be more common after external fixation. There is no data available comparing Steinmann pin and external fixation. Both fixation types show poor results in fracture reduction. Abstract: Introduction: Because of poor skin conditions and comorbidity, open reduction and internal fixation in ankle fractures is frequently contra-indicated in the elderly. This study reports the results of two temporary fixation types in fragility fractures in the older patient: transarticular Steinmann pin fixation and external fixation. Methods: Patients aged over 60 treated with a Steinmann pin or external fixation were retrospectively included. Patient, fracture and treatment characteristics were collected. Results: Fifteen patients were included. Nine were managed using a Steinmann pin and six by external fixation. All reached fracture consolidation. Patients treated with a Steinmann pin underwent a median of 2 operations and the pin was left in situ for 80 days. Three patients suffered from superficial wound infection. X-ray showed malreduction in 67% and only two patients returned to pre-injury mobility. A median of 2 operations with 32 fixation days was reported in the external fixation group. This group showed one deep infection. In 50% there was malreduction, one patient experienced disability in ambulation at the end of treatment. Conclusion: Both techniques show few complications, but have, as expected, poor results in fracture reduction and functional outcome. External fixation and subsequent internal fixation could result in better functional outcome.